Acoustic Characteristics of Coconut Leaf Beetle, Brontispa Longissima (Coleoptera: Chrysomelidae) - Selvaraj, Ganeshwari; Jalinas, Johari (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2024)
The coconut beetle, Brontispa longissima (Coleoptera: Chrysomelidae), is a serious pest of coconut trees, where the larvae and adults feed on coconut leaves. This activity produces vibrations that can be detected by acoustic equipment. This study aimed to identify the sound features between larvae and adults using temporal and spectral acoustic detection. Insect samples were collected from infested coconut trees in May 2021 in Penang, Malaysia. Acoustic recording activities were carried out at the Applied Entomology Laboratory using an AED-2010 sensor-preamplifier module. Parameters such as average impulse time, number of impulses, and average activity rate were recorded to examine the temporal aspect. Two parameters used in the spectral analysis were frequency range and dominant frequency (kHz). An Independent two-sample T-test was conducted to compare the mean differences in acoustic parameters between adult and larvae of B. longissima. The results showed that adult B. longissima was more active than larvae. It had higher mean impulse interval time (ms), mean number of impulses, and mean activity rate (impulses/s) than the larvae. However, the results showed that the difference in activity between larvae and adults was insignificant. Furthermore, this acoustic study is critical to understanding the behavior of destructive insects and helps develop more curative and sustainable methods to control B. longissima. Using acoustic methods could assist in evaluating the level of infestation and damaging activity of the insect pest.